2020
DOI: 10.1007/jhep01(2020)100
|View full text |Cite
|
Sign up to set email alerts
|

Non-derivative axionic couplings to nucleons at large and small N

Abstract: Among the possible CP-odd couplings of the axion to ordinary matter, the most relevant ones for phenomenology are the Yukawa couplings to nucleons. We analyze such non-derivative couplings within three complementary approaches: standard effective field theory, the Skyrme model and holographic QCD. In all the cases, the couplings can be related to the CP-odd non-derivative couplings to nucleons of the low-lying mesons and the η . Using the effective field theory approach we derive the expressions for the CP-odd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…In the following we will also consider a more general setup where part (if not all) of the flavor branes are not antipodal. In general, there can be several distinct flavor brane pairs as it happens in the recently considered Holographic QCD axion scenario [38,39].…”
Section: Kkmentioning
confidence: 99%
“…In the following we will also consider a more general setup where part (if not all) of the flavor branes are not antipodal. In general, there can be several distinct flavor brane pairs as it happens in the recently considered Holographic QCD axion scenario [38,39].…”
Section: Kkmentioning
confidence: 99%
“…The couplings of the axion with the nucleons and the photon have no UV contributions and are entirely determined by the low energy action and the mixing with the pseudoscalars. The magnitude of the couplings to nucleons have been estimated in [14].…”
Section: Discussionmentioning
confidence: 99%
“…can be induced whenever the Peccei-Quinn mechanism is not precise and an effective θ parameter is left over. In [14] it has been found that 27) whereḡ η N N andḡ πN N are the linear in θ CP-odd couplings of η and pions with nucleons. 10 To leading order in the chiral limit they reduce tō…”
Section: Axion Couplings To Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the emergent axion as an inflaton may be investigated along the lines of[94] 12. See also[95].…”
mentioning
confidence: 99%